2014
DOI: 10.1159/000360269
|View full text |Cite
|
Sign up to set email alerts
|

Initial Hemodialysis with a Temporary Catheter Is Associated with Complications of a Later Permanent Vascular Access

Abstract: The aim was to identify the risk factors of long-term vascular access complications. The study cohort consisted of 239 incident hemodialysis (HD) patients from 1998 to 2010 in a single center. Among these patients, 59.8% had initially been dialyzing with a temporary catheter. Within 3 months after starting dialysis, all catheters had been converted into permanent accesses. 45 patients incurred long-term access complications after the first 2 years of dialysis, and 34 (75.6%) had used a temporary catheter start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…A 2.77-fold risk of access-related complications including thrombosis and access failure using non-tCVC was reported at the beginning of HD [12]. However, the tCVC as long-term vascular access has been not included in previous research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2.77-fold risk of access-related complications including thrombosis and access failure using non-tCVC was reported at the beginning of HD [12]. However, the tCVC as long-term vascular access has been not included in previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Using a tCVC or non-tCVC at the initiation of HD was an independent risk factor for higher mortality than AVF [11]. Using non-tCVC in HD initiation would result in the occurrence of a side effect on a later permanent vascular access [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, we found that age was inversely associated with nonfunctional AV access after adjustment for the other covariates. Previous reports have showed less frequent AV fistula creation [ 7 ], poorer AV fistula maturation [ 30 ], and more long-term complications of vascular access [ 15 ] in the elderly. We believe that the relation seen between nonfunctional AV access and age in our study may partly reflect selection for AV access creation in elderly patients.…”
Section: Resultsmentioning
confidence: 99%
“…Most epidemiological studies have assessed factors associated with AV access use versus catheter without distinguishing between patients who had AV access created before dialysis and those who did not. Women, older patients, and those with cardiovascular diseases are more likely to start hemodialysis with a catheter [ 7 , 15 , 16 ]. Poor Fewer visits to a nephrologist and the lack of erythropoiesis-stimulating agent (ESA) in the predialysis period have also been associated with catheter use at hemodialysis initiation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the high complication rates associated with the use of CVCs [ 5 , 6 ], healthcare providers and organizations have encouraged and incentivized the use of non-catheter access via AVFs, or AVGs where an AVF is not feasible [ 4 ]. Once successfully created, an AVF or AVG may not remain patent.…”
Section: Introductionmentioning
confidence: 99%